The Similarities of Traditional Japanese and Indonesian Children's Games from the Point of View of Japanese Language Education Study Program Students - Nise Samudra Sasanti (Universitas Negeri Semarang, 2022)
This research aims: 1) To describe Japanese and Indonesian Traditional Children's Games from the point of view of students of the Japanese Language Education Study Program; 2) To learn the extent of understanding or knowledge students have about traditional games for Japanese and Indonesian children. The research method is an open and closed online questionnaire with first-semester student respondents from the 2020/2021 class of the Japanese Language Education Study Program of Universitas Negeri Surabaya. The results showed that the majority of students, as many as stated that they knew traditional children's games, both Japanese and Indonesian, well. Meanwhile, traditional children's games, both Japanese and Indonesian, include similarities in shape, materials, how to play the games, and similarities in benefits. The difference lies in form as well as the primary material. Keywords : Jurnal Pendidikan Bahasa Jepang Japanese Education JournalJapanese Traditional GameJapanese Indonesian Constrative StudiesJapanese Studies